IMPLEMENTASI UNDANG-UNDANG NOMOR 34 TAHUN 2004 TENTANG TNI - , AGUS SUBAGYO, Dr. Erwan Agus Purwanto, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The reformation era rolling sincenew order lead by Soeharto collapse in May 21st 1998 has was drive the huge swap in whole over living of society, nations, and states. The military power dominating an Indonesian political structure more than three decades was fail and moving toward the empowerment of civil society. Beginning the democratic political system in Indonesia is partial without concession of civilian supremacy over military that lead the impetus in attempt to establish the professional military. It is means that they are disengaged in politic, businesses, comply with the civil supremacy, law, and uphold the human right. All parties realizes that military reformation is a requirement and necessity that momentum of reformation must be the right time to push the military for exchange. An attempt to implement the military reformation is establish the regulation on Indonesian military. By the reasons, it is issued the Act No. 14 of 2004 on Indonesian National Army that approved by Assembly in September 30th 2004 passed by president in October 16th 2004. The Act No. 14 of 2004 is a substitution of the Act No. 2 of 1988 on Armed Forces of the Republic of Indonesia as the most important historical milestone in arranging the duty, role, and function of Indonesian National Army that is consistent with the modern democratic development in present. By the research, observer intend to highlight on how implementation of the crucial articles in national army law, such as territorial construction, empowerment, businesses, positional and structure, as well as troops deployment